Calcium sequestration by human platelet acidic organelles is regulated by the actin cytoskeleton and autocrine 5-hydroxytryptamine. (January 2022) - Sage, Stewart O.; Harper, Alan G.S.
Highlights: The pH gradient across acidic organelles is regulated upon human platelet activation. Autocrine 5-HT signalling triggers alkalinisation of platelet acidic organelles. Cytochalasin reduces ADP-evoked Ca 2+ release by increasing acidic organelle H + uptake. Abstract: Human platelets regulate agonist-evoked Ca 2+ signalling through Ca 2+ release from and sequestration into acidic organelles. Previous studies have pharmacologically characterised the presence of a Ca 2+ - H + exchanger in these organelles. This exchanger appears to regulate a secondary plateau phase in agonist-evoked cytosolic Ca 2+ signals in fura-2-loaded human platelets. Here we demonstrate that cytochalasin D treatment removes the secondary plateau in ADP-evoked Ca 2+ signals elicited in the absence of external Ca 2+ . This effect was reversed by pretreatment with nigericin, a K + / H + exchanger that short-circuits the Ca 2+ - H + exchanger. Using Fluo-5N- or Lysosensor Green-loaded cells, cytochalasin D was found to enhance Ca 2+ sequestration into acidic organelles by preventing their alkalinisation. Additional experiments demonstrated that ADP-evoked alkalinisation of acidic organelles and subsequent slowing of acidic organellar Ca 2+ sequestration was mediated by autocrine 5-HT signalling. Enhancing this 5-HT signalling using fluoxetine overcame the inhibitory effect of cytochalasin D on ADP-evoked Ca 2+ signals, indicating that cytochalasin D interferes with 5-HT autocrine signalling. The ability of Cytochalasin D to interfere with autocrine 5-HT signalling was downstream of the 5-HT2A receptor as secretion of [ 3 H]-5-HT from ADP-stimulated human platelets was not reduced. These data provide the first evidence that the pH gradient across acidic organelles is dynamically regulated upon human platelet activation, and that this can play a significant role in controlling human platelet function by modulating Ca 2+ - H + exchange and so [Ca 2+ ]i . Graphical abstract: Image, graphical abstract